A PANEL DATA ANALYSIS FOR CONVENTIONAL AND PARTICIPATION BANKS : AN ANALYSIS BASED ON TURKISH BANKING SECTOR (Third Sector Social Economic Review, 2019)
Participation banks in Turkey, named also as interest-free banking, started to develop in mid-1980s. Considering how they perform especially in terms of interest–free applications, participation banks fully diverge from their conventional counterparts and started to become more significant in the context of global financial system. Based on profit-loss ground, participation banks completely exclude interest-related applications and take this principle into account in developing all other financial instruments. Incresasing share of participation banking both in Turkish banking system and in global financial system motivate researchers to analyze performance differences between two banking types. In this respect, the aim of this paper to scrutinize the points where two important components of the financial system differs from each other and to reveal performance determinants of conventional and participation banks.
Keywords: Conventional Banking; Participation Banking; Interest-Free Principle; Panel Regression Analysis